A novel combination of silane‐coated silica colloid with hybrid RNA extraction protocol and RNA enrichment for downstream applications of spermatozoal RNA. (14th May 2018) - Vijayalakshmy, K.; Kumar, P.; Virmani, M.; Pawaria, S.; Lalaji, N. S.; Sharma, P.; Rajendran, R.; Yadav, P. S.; Kumar, D.
Summary: Spermatozoa are specialised cells with low RNA content as compared to somatic cells. The suitable sperm RNA extraction and enrichment protocols for downstream applications are available for human, cattle, stallion and mouse but not for buffalo spermatozoa. Therefore, the present work was conducted to find out suitable colloidal solution for sperm purification and appropriate protocol for sperm RNA extraction and enrichment/amplification of RNA. For purification, we used PVP‐coated silica colloidal solution (PVP‐Si), silane‐coated silica colloidal solution (Silane‐Si) and iodixanol. Sperm recovery rate, total sperm motility and progressive sperm motility were significantly improved after separation by Silane‐Si and iodixanol compared to PVA‐Si method. The combined guanidinium thiocyanate–phenol–chloroform (GTPC) with silica matrix (SM)‐based RNA extraction yielded more quantity of RNA in compared to individual method. The hybrid of SM and GTPC into a single protocol yielded 360–450 ng RNA from 30 million buffalo spermatozoa. For the first time, we adopted new way to enrich sperm RNA that increased the RNA concentration 4–5 times that was sufficient for downstream applications. The linear amplification of sperm RNA increased RNA concentration around 27–45 times. In summary, Silane‐Si colloid for sperm separation, hybrid SM and GTPC protocol for sperm RNA extraction followed by enrichment or amplification of RNA was found suitable for high‐throughput analyses of buffalo sperm RNA.